(untitled) (Journal of humanities and social sciences exploratio, 2025)
This paper focuses on the interactive mechanism between the inheritance of humanistic values and the construction of social identity in the field of journalism and communication. It analyzes the internal logic and practical approaches of their mutual promotion. The research finds that news media, through the activation of cultural memory, story-telling narrative, and innovative expression, achieve the modern transformation of humanistic values. They also strengthen social identity by relying on emotional resonance, symbol construction, and ritual communication. Such interaction builds a bidirectional spiral model of "value inheritance - identity construction". Traditional media and new media present a complementary functional trend. This study provides a new perspective for understanding the social and cultural functions of journalism and communication.